A case study of the mesospheric 6.5-day wave observed by radar systems - Jiang, G.; Xu, Jiyao; Xiong, J.; Ma, R.; Ning, B.; Murayama, Y.; Thorsen, D.; Gurubaran, S.; Vincent, R. A.; Reid, I.; Franke, S. J. (My University, 2008)
[1] In this paper, analysis of wind data detected by six ground-based radar systems located in equatorial and midlatitude belts shows that a strong mesospheric 6.5-day wave event occurred during April–May 2003. We compared the global distribution of the observed 6.5-day wave event with the theoretical wave structure (Rossby normal mode (s, n) = (1, −2)). Additionally, we investigated several important wave characteristics to understand the mesospheric 6.5-day wave event, i.e., wave period, vertical structure, relationship with background wind, propagating direction, and the zonal wave number. Our results are summarized into three points: (1) the latitudinal structure of the mesospheric 6.5-day wave during April–May 2003 is basically in agreement with the theoretical Rossby mode (s, n) = (1, −2), although the wave amplitude of zonal wind peaked at the subequatorial latitude of Northern Hemisphere but not at the theoretical place, equatorial region; (2) the main wave periods and the altitude distribution of large amplitude of this wave event varied with latitude; (3) the downward propagating wave phases indicated that this wave event originated in the lower atmosphere and propagated upward to the upper region.
Keywords: Atmospheric processes; Planetary waves; Mesospheric dynamics; Radar systems